2020
DOI: 10.3390/ani11010056
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Temperature and Humidity on the Performance and Physiology of Laying Hens

Abstract: We investigated the effect of different ambient temperatures and relative humidity (RH) with the same temperature-humidity indices (THI) on laying performance, egg quality, heterophil to lymphocyte ratio (H/L ratio), corticosterone (CORT) concentration in blood, yolk, and albumen, and plasma biochemical parameters of laying hens. Commercial hens (Hy-Line Brown; n = 120), aged 60 weeks, were allocated to two environmental chambers. Laying hens were subjected to either one of two thermal treatments—26 °C and 70%… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
0
16
1
Order By: Relevance
“…In the present study, we studied the hormone-hematological features of the stress response in the body of laying hens under conditions of an excessive increase in the density of bird laying in the cage. This initiated the appearance of heat stress signs in them, as a result of the absence of sweat glands, the presence of feathers, and the dependence of thermal regulation on the respiratory rate [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we studied the hormone-hematological features of the stress response in the body of laying hens under conditions of an excessive increase in the density of bird laying in the cage. This initiated the appearance of heat stress signs in them, as a result of the absence of sweat glands, the presence of feathers, and the dependence of thermal regulation on the respiratory rate [15].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the immunosuppressive effects of corticosterone in birds are realized both at the level of humoral and cellular components of immunity [4], determining the effectiveness of their responses. According to [14][15][16], the severity of the primary response of birds to stressor action reflects the ratio between heterophiles and lymphocytes. This is the result of glucocorticoid-induced rapid apoptosis of lymphocytes [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major factor that negatively affects broiler chickens production in the subtropics and tropics is heat stress (Aluwong et al, 2017;Goel et al, 2021;Sugiharto et al, 2017). The combined effects of high relative humidity (RH) and high ambient temperature (AT) have been reported to induce thermal stress in chickens (Egbuniwe et al, 2015;Jiang et al, 2020;Kim et al, 2021;Qaid et al, 2021), therefore, lipid peroxidation resulting from hyperthermia may damage some of their vital organs (Rhoads et al, 2013;Al-Zghoul & Saleh, 2020;Aksoy et al, 2021;Gogoi et al, 2021). Antioxidants are used universally in dietary supplementation, and these supplements are beneficial in ameliorating tissue damages induced by stress (Gouda et al, 2020;Sun et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The above studies identified the correlation between temperature control and ammonia concentration to livestock and poultry breeding management, which can effectively improve laying rate and egg quality. Kim et al [12] showed that environmental variables of temperature and humidity had a significant influence on laying rate, which provided a scientific basis for management decisions. Guo et al [13] studied the influence of temperature on laying ducks based on the parallel vector regression prediction model.…”
Section: Introductionmentioning
confidence: 99%